Contributions to the Psychology of the Cinemagoer - Blaustein, Leopold (Phainomena (Ljubljana), 2025)
The text aims to describe the experiences of the cinemagoer by analyzing complexes of lived experiences as being composed of presentations, feelings, and judgments. These experiences are discussed with regard to the status of sensations and the object constituted by the goer. The study examines the types and features of experiences expressed by film characters by scrutinizing the theory of sympathy (Einfühlung). Moreover, the status and meaning of music in the cinemagoer’s lived experiences is explored; in this respect, the author argues that music is an important factor in shaping the goer’s mood. The text determines non-aesthetic and “semi-aesthetic” factors, which are combined in the cinemagoer’s lived experiences, and inquires into the status of the world of cinematic art.
Keywords: aesthetic experience; assumption; cinematic art; domišljijski svet; domneva; estetsko izkustvo; feeling; imaginative world; kinematografska umetnost; občutje; pleasure; predstava; presentation; užitek